Three-Dimensional Non-Linear Analysis based on the Temporal Evolution of an RCC Dam Including the Alluvium Effect - ADJADJ, Mustapha; ALIOUCHE, Yaaqoub; MEKSAOUINE, Mohamed (GeoScience Engineering, 2021)
This article discusses the seismic response of roller-compacted concrete dams by interpreting their behaviour under the effect of static and dynamic loads applied to a real case study: the Boussiaba dam. A three-dimensional finite element numerical modelling was undertaken using the Midas GTS- NX 2017 calculation code. The geometric model was established in Autocad taking into account the actual geomorphology of the terrain and the existing dam and then exported to GTS-NX. The dynamic solicitation, i. e. the earthquake, was generated from two accelerograms 0.25 g and 0.35 g amplitude respectively recorded in the Mila region located less than 20 km from the dam site. The initial static load being constituted by the dead weight, the water thrust and the sludge thrust at the bottom of the dam. Several reference points were chosen on the dam body to study the different parameters adopted. The results obtained during the dynamic numerical analysis show that the overall behaviour of the dam during earthquakes was satisfactory, without endangering the structural integrity of the structure. Keywords: Dynamic; Finite elements; Midas GTSnx; RCC dam; Three-dimensional. DOI 10.35180/gse-2021-0047